2022
DOI: 10.1108/aeds-01-2021-0019
|View full text |Cite
|
Sign up to set email alerts
|

The Sino-African higher education exchange: toward building a literature

Abstract: PurposeThis paper intends to provide a thematic literature review of the scholarly research articles orbiting the Sino–African education cooperation and exchange, published between 2005 and 2022.Design/methodology/approachThe methodology used in this paper is qualitative in nature with a thematic approach. The author used content analysis techniques to spotlight the major themes of the topic studied. The author selected the papers and theses, based on their heuristic capacity, from two major databases for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
0
2
0
1
Order By: Relevance
“…Similarly, Roy et al (2019) review studies on the various outcomes students who participate in short-term ISM programmes face and group these outcomes into broad categories related to cultural, personal and career/employment outcomes. Furthermore, the other side of the review studies has focused on ISM approaches and experiences unique to specific regions or countries (e.g., Baek et al, 2021;Bouchaib, 2023;Browne et al, 2015;Knight-Grofe & Deacon, 2016;Russell et al, 2021). Interestingly, few bibliometric reviews on the domain were recently reported (e.g., Gümüş et al, 2020;López-Duarte et al, 2021;Pham et al, 2021).…”
Section: Review Of Past Reviews On Ismmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Roy et al (2019) review studies on the various outcomes students who participate in short-term ISM programmes face and group these outcomes into broad categories related to cultural, personal and career/employment outcomes. Furthermore, the other side of the review studies has focused on ISM approaches and experiences unique to specific regions or countries (e.g., Baek et al, 2021;Bouchaib, 2023;Browne et al, 2015;Knight-Grofe & Deacon, 2016;Russell et al, 2021). Interestingly, few bibliometric reviews on the domain were recently reported (e.g., Gümüş et al, 2020;López-Duarte et al, 2021;Pham et al, 2021).…”
Section: Review Of Past Reviews On Ismmentioning
confidence: 99%
“…Furthermore, the other side of the review studies has focused on ISM approaches and experiences unique to specific regions or countries (e.g., Baek et al, 2021; Bouchaib, 2023; Browne et al, 2015; Knight-Grofe & Deacon, 2016; Russell et al, 2021). Interestingly, few bibliometric reviews on the domain were recently reported (e.g., Gümüş et al, 2020; López-Duarte et al, 2021; Pham et al, 2021).…”
Section: Review Of Past Reviews On Ismmentioning
confidence: 99%
“…До недавнего времени страна была лидером только по числу студентов, отправленных для обучения за рубеж, а в последние годы Китай стал заметным игроком в экспорте образования, предоставляя государственные стипендии студентам из развивающихся регионов. Особое место в продвижении экспорта китайского образования, по мнению С. Бучаиба (Bouchaib, 2023), занимают страны Африки (регион традиционных интересов экспорта российского образования). Анализу эффективности реализации стратегии экспорта образования Сингапура посвящена работа Х. Ли и Б. Эдвардса (Le, Edwards, 2023).…”
Section: материалы и методыunclassified